A STUDY ON ASSEMBLAGE OF INVERTEBRATES INHABITING ROCKY SHORES WITHIN THE PORT- LIMIT OF PORT- LOUIS, MAURITIUS - Julia Charles; Chandani Appadoo; Asha Poonyth Poonyth (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Rocky shores provide an important habitat for marine organisms. This study aimed at providing baseline data on assemblage of organisms on rocky shores within the port-limit of Port-Louis, Mauritius. Four rocky shores, with three at Pointe aux Sables (La Pointe1, La Pointe2, and Petit Verger) and one at Baie du Tombeau were studied from October 2007 to February 2008. On each site three stations, located at intervals of 2m, with an area of 40m2 each were set up. Intertidal organisms were hand-collected within forty-eight, 1m2 quadrat for invertebrates. Observations of 16,061 specimens led to identification of 30 faunal species belonging mostly to phyla Mollusca and Arthropoda. Mean total abundance of invertebrates per 1m2 varied from 729.22±173.07 at la Pointe2 to 143.97±11.43 at Baie du Tombeau. The gastropod, Planaxis sulcatus was the most abundant species at La Pointe1 and Petit Verger with mean abundance of 196.86±179.71 and 168.10±113.44 per 1m2 respectively. The bivalve, Modiolus auriculatus was the dominant species with mean abundance of 673.33±762.04 per 1m2 at La Pointe2 and Nerita punctata was most abundant (39.41±57.35 per 1m2) at Baie du Tombeau. Lowest Shannon diversity was observed La Pointe 2. The study is useful for future work on port area.